ففتھ جنریشن وار فئیر اور اس کے اہم ذرائع (اسلامی تعلیمات اور عصر حاضر کے تناظر میں): Fifth Generation Warfare and its Important Sources (Islamic Teachings and Contemporary context) - Awan, Hafiz Ahmad Saeed Awan; Barvi, Dr. Muhammad Ramzan Najam (Al-Irfan, 2023)
Fifth generation warfare is conducted by psychological tactics. This war is primarily fought through non-kinetic military action such as misuse of social media, spreading misinformation, cyberattacks along with emerging technologies like artificial intelligence and fully autonomous systems. The term “fifth generation warfare” was first time used in 2010 by Lieutenant Colonel Alberts who was American army officer and theorist. The concept of four generations in the history of modern warfare was created by a team of United States analysts including William S. Lind in 1989 for the purpose of an argument that changing face of war entering into a fourth generation. The intention behind fifth generation war is to use latest technology of current era as well as save all resources which are used in physical warfare. Keywords: Fifth generation warfare, non-kinetic military action, social media, cyberattacks, artificial intelligence, Lieutenant Colonel Alberts, William S. Lind